Dual regulation of the expression of the polyubiquitin gene by cyclic AMP and heat shock in yeast. - Tanaka, K (1988)
The expression of the polyubiquitin gene in yeast, UB14, is repressed by cAMP-dependent protein phosphorylation. Since cycloheximide does not inhibit the induction of the UB14 transcription, no de novo protein synthesis is required in this process. The expression of the UB14 gene is also induced by mild heat shock by a mechanism other than depletion of cAMP. From the genetic analysis of the UB14 gene, we propose that the UB14 gene is one of the genes which are part of the cAMP-effector pathway and required for G0/G1 arrest in Saccharomyces cerevisiae.